2011
DOI: 10.1111/j.1476-5381.2011.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of body weight, liver steatosis and expression of stearoyl‐CoA desaturase 1 by the isoflavone daidzein in diet‐induced obesity

Abstract: BACKGROUND AND PURPOSE The lack of safe and effective treatments for obesity has increased interest in natural products that may serve as alternative therapies. From this perspective, we have analysed the effects of daidzein, one of the main soy isoflavones, on diet‐induced obesity in rats. EXPERIMENTAL APPROACH Rats made obese after exposure to a very (60%) high fat‐content diet were treated with daidzein (50 mg·kg−1) for 14 days. The dose was selected on the basis of the acute effects of this isoflavone on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 58 publications
11
77
0
1
Order By: Relevance
“…The gene expression of SCD-1 was decrease in high fat diet group, our study is coincides with the study of A. Crespillo et al (36), in their study the expression of SCD-1 was decrease in the liver of the mice fed with high fat diet. They concluded that the HFD causes reduction in the expression of FAS, ACC, and SCD-1.…”
Section: )supporting
confidence: 93%
“…The gene expression of SCD-1 was decrease in high fat diet group, our study is coincides with the study of A. Crespillo et al (36), in their study the expression of SCD-1 was decrease in the liver of the mice fed with high fat diet. They concluded that the HFD causes reduction in the expression of FAS, ACC, and SCD-1.…”
Section: )supporting
confidence: 93%
“…To dismiss that NP-1 reduced food intake by inducing a nonspecific state of behavioral suppression, we performed a conditioned taste aversion test showing that NP-1 was not an aversive drug. Presently, we cannot establish a direct role for NP-1-released adiponectin in the suppression of food intake, although preliminary results with four different types of drugs that increase adiponectin levels, including the isoflavone daidzein and the cannabinoid CB1 receptor antagonist AM251, reflect that pharmacological induction of adiponectin release is associated with reduction of food intake (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Both adipose tissue and the liver showed marked changes after treatment with daidzein, affecting transcription factors and lipogenic enzymes, particularly stearoyl coenzyme A desaturase 1 – considered a pivotal enzyme in obesity. Expression of UCP1, an important enzyme for thermogenesis, was increased in brown adipose tissue after daidzein treatment (Crespillo et al , 2011). …”
Section: Examples Of Natural Thermogenic Agentsmentioning
confidence: 99%